Towards an inclusive and culturally sensitive conceptualisation of sexual well-being of young people: preliminary framework development using a modified Delphi methodology - Lore Remmerie; Guncha Annageldiyeva; Kayleigh Grossman; Caesar Kaba Kogoziga; Nicole Leonetti; Ana Mosiashvili; Shreya Shrestha; Tisungane Sitima; Evi Stuckens; Michael Tetteh Doku; Aslan Temirkhanov; Diana Marcela Zambrano; et al. (Sexual and Reproductive Health Matters)
This study aims to contribute to the development of a comprehensive framework for sexual well-being of young people. By making space for diverse young people’s perspectives through co-creating the framework, we seek to enhance the understanding of sexual well-being in sexual and reproductive health and rights (SRHR) research in a culturally sensitive and inclusive way. A modified Delphi study invited SRHR young professionals (aged 18–30) with different backgrounds to participate as experts in three rounds of online discussions. A framework of sexual well-being was co-created by 15 young professionals from countries across Europe, Asia, Africa, and South America. This framework recognised sexual well-being as a subjective concept with different meanings: for example, by applying an open understanding of sexual activity, and intimacy. It also acknowledged the challenges individuals face in fully understanding and achieving their sexual well-being, due to societal injustices. The framework outlined key capabilities inherent to sexual well-being, including informed decision-making, bodily autonomy, consent, exploration, self-awareness, pleasure, communication, comfort, safety, and self-esteem. Considering that these capabilities can only be realised within an enabling environment, access to sexual health information and services, as well as acceptance, respect, safety, and freedom from coercion and violence, were included as a key part of the framework. This study captured young people’s views on sexual well-being to co-create a culturally sensitive framework. This framework recognises different interpretations of sexual well-being, and focuses on supportive environments that empower individuals to define and pursue sexual well-being in a way that honours their experiences and needs.